On How Hot Towers Fuel the Hadley Cell: An Observational and Modeling Study of Line-Organized Convection in the Equatorial Trough from TOGA COARE - Fierro, Alexandre O.; Simpson, Joanne; LeMone, Margaret A.; Straka, Jerry M.; Smull, Bradley F. (Journal of the atmospheric sciences, 2009)
An airflow trajectory analysis was carried out based on an idealized numerical simulation of the nocturnal 9 February 1993 equatorial oceanic squall line observed over the Tropical Ocean and Global Atmosphere Coupled Ocean–Atmosphere Response Experiment (TOGA COARE) ship array. This simulation employed a nonhydrostatic numerical cloud model, which features a sophisticated 12-class bulk microphysics scheme. A second convective system that developed immediately south of the ship array a few hours later under similar environmental conditions was the subject of intensive airborne quad-Doppler radar observations, allowing observed airflow trajectories to be meaningfully compared to those from the model simulation. The results serve to refine the so-called hot tower hypothesis, which postulated the notion of undiluted ascent of boundary layer air to the high troposphere, which has for the first time been tested through coordinated comparisons with both model output and detailed observations. For parcels originating ahead (north) of the system near or below cloud base in the boundary layer (BL), the model showed that a majority (>62%) of these trajectories were able to surmount the 10-km level in their lifetime, with about 5% exceeding 14-km altitude, which was near the modeled cloud top (15.5 km). These trajectories revealed that during ascent, most air parcels first experienced a quick decrease of equivalent potential temperature (θe) below 5-km MSL as a result of entrainment of lower ambient θe air. Above the freezing level, ascending parcels experienced an increase in θe with height attributable to latent heat release from ice processes consistent with previous hypotheses. Analogous trajectories derived from the evolving observed airflow during the mature stage of the airborne radar–observed system identified far fewer (∼5%) near-BL parcels reaching heights above 10 km than shown by the corresponding simulation. This is attributed to both the idealized nature of the simulation and to the limitations inherent to the radar observations of near-surface convergence in the subcloud layer. This study shows that latent heat released above the freezing level can compensate for buoyancy reduction by mixing at lower levels, thus enabling air originating in the boundary layer to contribute to the maintenance of both local buoyancy and the large-scale Hadley cell despite acknowledged dilution by mixing along updraft trajectories. A tropical “hot tower” should thus be redefined as any deep convective cloud with a base in the boundary layer and reaching near the upper-tropospheric outflow layer.